2020
DOI: 10.2196/15845
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Low-Intensity, Internet-Based Psychological Interventions for the Treatment of Depression in Primary Care: Randomized Controlled Trial

Abstract: Background Primary care is a major access point for the initial treatment of depression, but the management of these patients is far from optimal. The lack of time in primary care is one of the major difficulties for the delivery of evidence-based psychotherapy. During the last decade, research has focused on the development of brief psychotherapy and cost-effective internet-based interventions mostly based on cognitive behavioral therapy (CBT). Very little research has focused on alternative metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…The aim of the original study was to assess the effectiveness of three low-intensity intervention programs applied by ICTs (Healthy Lifestyle Program, Positive Affect Promotion Program and Mindfulness Program) compared with a control condition. The research protocol and main results have been reported elsewhere [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the original study was to assess the effectiveness of three low-intensity intervention programs applied by ICTs (Healthy Lifestyle Program, Positive Affect Promotion Program and Mindfulness Program) compared with a control condition. The research protocol and main results have been reported elsewhere [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Ethical Review Board of the regional health authority approved the study (Ref: IB 2144/13 PI). More details about the study design, recruitment, randomization and data collection procedure are described elsewhere [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found significant reductions of depressive symptoms also through the delivery of mindfulness-based online interventions (Questret, Cropley, & Fife-Schaw, 2018;Gili et al, 2020;Shankaland et al, 2020). Again, considering anxiety features, several studies demonstrated the efficacy of web-and app-based psychological interventions on anxiety reduction (e.g., Questret, Cropley, & Fife-Schaw, 2018;Rasanen et al, 2016;Lopez et al, 2019;Nissen et al, 2019;Kladnitski et al, 2020).…”
Section: Italiamentioning
confidence: 96%
“…Given the potential of IBIs as low-intensity interventions in PC, we conducted a randomized control trial (RCT) in a sample of patients diagnosed with MDD in different PC settings in Spain [28]. In this study, we examined the effectiveness of three low-intensity IBIs (PA promotion vs. healthy lifestyle vs. mindfulness) along with improved treatment as usual (iTAU), compared to iTAU alone, and the results were promising [29]. Specifically, healthy lifestyle and mindfulness interventions were effective in reducing depression severity, compared to iTAU, at post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is a secondary analysis of the RCT carried out by Gili et al [29]. More specifically, this study carries out an in-depth examination of the role of a specific IBI to promote PA as an adjunct therapy to iTAU in PC settings, given PA's potential as a strategy to improve well-being in MDD patients.…”
Section: Introductionmentioning
confidence: 99%